Improvement of native pasture with sodseeding of temperate species - Fontaneli, Renato Serena; Jacques, Aino Victor Avila (Pesquisa Agropecuaria Brasileira, 1991)
The effect of sodseeding of Lolium multiflorum Lam., Avena strigosa Thell, Avena sativa L., Trifolium subterraneum L., T. vesiculosum Savi, T. pratense L. and T. repens L. on dry matter (DM), crude protein (CP) and soil vegetation coverage was studied under field conditions at the Experimental Station of UFRGS, Eldorado do Sul, RS, southern Brazil, using a randomized block experimental design with four repetitions and 40 m2 plots. Evaluations were made every eight weeks, with ground level cuttings. All introduced species with the exception of Trifolium subterraneum L., poorly established, increased the availability of MS and PB in native pastures. The introduction of temperate species improved the annual production distribution of forage. The content and availability of crude protein of introduced species surpassed that of native species. The vegetation cover of the soil was little effected by the introduction of the forage species and decreased from an average of 21%, in the first evaluation, to less than 3% after the second evaluation.